Incidental finding of paradental cyst in the maxillary anterior teeth during immediate implant placement - Phebie Asta Rodrigues; Ashwin Parakkaje Subramanya; M L V Prabhuji; Karthikeyan Bangalore Vardhan (Wolters Kluwer Medknow Publications, 2022)
Paradental cyst is classified as an inflammatory cyst, and its occurrence in the anterior maxillary region is very rare. Several hypotheses have been put forward on the etiopathogenesis among which the formation of cyst secondary to inflammatory destruction of the periodontium and alveolar bone can be attributed to the present case. A 26-year-old male patient reported with loosened maxillary anterior teeth. After clinical and radiological examination, extraction of teeth #12, #11, #21, and #22 followed with immediate implant placement was planned. During extraction of #21, incidentally, a cyst was noted to be attached to the apices of #21 tooth. Implants were placed at #12, #11, and #22 sites, and socket of #21 was debrided thoroughly, followed by the placement of graft. A histopathological study of the cyst revealed it to be a paradental cyst. The patient was followed up for 6 months, and no recurrence of cystic lesion was noted. When immediate implant placement is being planned, considerations to the periodontal and periapical disease status of the teeth being extracted are crucial to achieve better treatment outcomes.